PUBLIC ACCOUNTANCY IN HONG KONG. - Sih, S. T. (The Accounting Review, 1962)
Abstract Public accountancy in Hong Kong may be divided into three major parts, auditing, taxation and costing. Costing is a special feature of public accountancy in Hong Kong. It is associated with exports under the Commonwealth Preference scheme. Auditing in Hong Kong may be either compulsory or voluntary. The proper title of a public accountant engaged in company auditing is the "authorized auditor," an official list is kept by the companies' registry and published yearly in the government's December gazette. The official accounting body in Hong Kong is the Authorized Auditors Board. The application of statistical techniques, sampling, probability control, etc., to auditing has not received enough attention, but the popular method of direct confirmation used in the United States is also widely accepted in Hong Kong. Income tax supplies the largest portion of the total Hong Kong revenue, although the rate is quite low. The standard rate of tax is now 12.5%, a rate unchanged since 1951. Profits tax is charged on every individual, partnership or corporation carrying on business in Hong Kong.